The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1470-6431.2007.00587.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐cultural evaluation of factors driving intention to purchase new food products – Beijing, China and south‐east England

Abstract: It has been reported that consumers in different countries have distinctive perceptions of, and attitudes to, products. This study investigated consumers’ thoughts on new food products in south‐east England (n = 222) and Beijing, China (n = 139), using a questionnaire‐based largely on the Theory of Reasoned Action. Results indicated that consumers in both countries believe it is necessary for the food industry in their respective countries to introduce new food products and they would like to try new products.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 30 publications
(82 reference statements)
2
31
0
Order By: Relevance
“…In other words, these consumption behaviours may not indicate social status so that they are not greatly influenced by other people's opinions. Similarly, Eves and Cheng (2007) found that Chinese consumers' personal beliefs were more important in intention to purchase new food products than the influences of other people, which did not support their expected results that the Chinese would place more emphasis on others' opinions than on their own beliefs due to China being a collectivist culture (Eves and Cheng, 2007). They reasoned that food is not an item of conspicuous consumption or a cultural shift among urban Chinese (Eves and Cheng, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, these consumption behaviours may not indicate social status so that they are not greatly influenced by other people's opinions. Similarly, Eves and Cheng (2007) found that Chinese consumers' personal beliefs were more important in intention to purchase new food products than the influences of other people, which did not support their expected results that the Chinese would place more emphasis on others' opinions than on their own beliefs due to China being a collectivist culture (Eves and Cheng, 2007). They reasoned that food is not an item of conspicuous consumption or a cultural shift among urban Chinese (Eves and Cheng, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies (Kim et al, 2006;Eves and Cheng, 2007) have confirmed that 5-point Likert scales are comprehensible with Chinese consumers, and widely applied in Chinese food consumption studies (Sun and Collins, 2002;Eves and Cheng, 2007). Hence, it was decided to use such scales to evaluate the strength of respondents' agreement to the statements in the survey instrument.…”
Section: Methodology Measuresmentioning
confidence: 99%
“…In general, considerable differences exist between cultures in terms of the perception of attractiveness of food from other cultures [67]. For Chinese consumers, food that is different in taste, culture and quality is fashionable and desirable [102]. However, not all Chinese visitors are eager to try local food.…”
Section: Managerial Implicationsmentioning
confidence: 99%